Interações entre aves frugívoras e plantas em um fragmento de mata atlântica de Minas Gerais - Fadini, Rodrigo Ferreira [UNESP]; De Marco Jr., Paulo (My University, 2004)
We studied the frugivorous birds and their fruiting plants during two years in a forest fragment in Viçosa, Minas Gerais State, Brazil. Our aim was to identify the importance of birds and plants based on an importance index that comprise both the number of interactions and interaction exclusiveness. Twentynine bird species and 25 plant species were recorded. Small birds (< 100 g) comprised 85% of the interactions, and Chiroxiphia caudata reached the largest importance index (0.296), with 12 interactions, being six exclusive. Among plants, the melastome Miconia cinnamomifolia reached the largest importance index (0.277), interacting with 72.4% (21) of the bird species. This study showed that seed dispersal by small birds couldn't be underestimated because they disperse seeds of many plant species, even in pristine forests. Studies like this are also important to list the main food resources to frugivorous birds that could be used in management plans.
Interactions among frugivorous birds and plants in an Atlantic Forest fragment of Minas Gerais State
Keywords: Atlantic Forest; Forest fragmentation; Frugivorous birds; Seed dispersal; Aves; Chiroxiphia caudata; Miconia cinnamomifolia